Paparan Pestisida dan Kejadian Mild Cognitive Impairement (MCI) pada Remaja di Daerah Pertanian di Kecamatan Sumowono - Siswanto, Yuliaji; Kartika Dian Pertiwi; Sri Lestari (Pro Health Jurnal Ilmiah Kesehatan, 2024)
Mild Cognitive Impairment (MCI) is a condition of objective cognitive impairment with clinical symptoms leading to dementia. This condition is characterized by problems with memory function, language, thinking or judgment (executive function) and spatial perception (visuospatial). Exposure to pesticides can have an impact on human health, especially the health of farmers. The impact of pesticides on people who are constantly exposed can cause nervous disorders, liver disorders, hormonal system disorders, and increased blood pressure. The aim of this study was to determine the relationship between exposure to pesticides and the incidence of  Mild Cognitive Impairment (MCI) in adolescents around agricultural areas in Sumowono District. The research design used was observational with a cross-sectional time approach. The research sample was 35 teenagers taken purposively. Data were analyzed using the Spearman Rank correlation test. The results showed that there was no significant relationship between pesticide exposure and the incidence of mild cognitive impairement (MCI) (r=0,018; p=0,919). The conclusion of this study is that there is no relationship between exposure to pesticides and the incidence of mild cognitive impairment (MCI) in adolescents in agricultural areas in Sumowono District ABSTRAK                 Gangguan Kognitif Ringan atau Mild Cognitive Impairent (MCI) merupakan suatu kondisi gangguan kognitif obyektif dengan gejala klinis menuju terjadinya dimensia (kepikunan). Kondisi ini ditandai dengan masalah fungsi memori, Bahasa, pemikiran atau penilaian (fungsi eksekutif) dan persepsi ruang (visuospasial). Paparan pestisida dapat berdampak bagi kesehatan manusia terutama kesehatan petani. Dampak pestisida pada orang-orang yang selalu terpapar dapat menyebabkan gangguan syaraf, gangguan hati, gangguan sistem hormon, dan kenaikan tekanan darah. Tujuan pada penelitian ini adalah untuk mengetahui hubungan paparan pestidida dengan kejadian MCI pada remaja di sekitar daerah pertanian di Kecamatan Sumowono. Desain penelitian yang dugunakan adalah observasional dengan pendekatan cross sectional. Sampel penelitian sebanyak 35 remaja yang diambil secara purposive. Data dianalisis menggunakan uji korelasi Spearman Rank. Hasil penelitian menunjukkan tidak ada hubungan yang bermakna antara paparan pestisida dengan kejadian MCI (r=0,018; p=0,919). Simpulan dalam penelitian ini adalah tidak ada hubungan antara paparan pestisida dan kejadian mild cognitive impairement (MCI) pada remaja di daerah pertanian di Kecamatan Sumowono.